People, nation and state the meaning of ethnicity and nationalism - edited by Edward Mortimer (London I.B. Tauris, 1999)
While conflicts of class, ideology and political systems have receded in the post-Cold War world, divisions based on group identity--cultural, ethnic, religious, and national--have assumed new importance. From Bosnia to Belfast and Burundi, from California to Kazakhstan, the difficulty of defining and reconciling group identities, and relating them to state structures, has become one of the central problems of our time. In this book, leading scholars and writers have collaborated with Edward Mortimer to illuminate the issues of ethnic and national identity that have emerged as central to the politics of today?s world.
Includes bibliographical references and index.
Keywords: Nationalism; Ethnicity; Nation-state; Political Science; POLITICAL SCIENCE -- Political Ideologies -- Nationalism; Ethnicity; Nation-state; Nationalism